2019
DOI: 10.1093/scan/nsz054
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve-mediated neural modulation of emotional control and regulation in people with late-life depression

Abstract: Late-life depression (LLD) is an affective disorder that is highly prevalent among older people. Cognitive reserve (CR) refers to an active process that facilitates the flexibility and efficiency of the neural networks to compensate for impairments that emerge in consequence of brain pathology. The current functional magnetic resonance imaging study investigated whether and how CR affects emotional regulation, level of depression severity and neural activity associated with affective control during emotional S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 96 publications
(144 reference statements)
5
20
0
1
Order By: Relevance
“…No group×valence analysis was reported. Finally, in 55 people with LLD and 40 controls, using an eStroop, 50 controls were more accurate and had shorter latencies. There was no effect of emotion on accuracy, but there was on latency, with both positive and negative words associated with longer latencies.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…No group×valence analysis was reported. Finally, in 55 people with LLD and 40 controls, using an eStroop, 50 controls were more accurate and had shorter latencies. There was no effect of emotion on accuracy, but there was on latency, with both positive and negative words associated with longer latencies.…”
Section: Resultsmentioning
confidence: 86%
“…Participants with depression ( n = 33) showed greater subgenual cingulate activity during affective processing compared with controls ( n = 27) with a significant correlation between white matter hyperintensity and activity. Huang et al 50 (55 participants with LLD, 40 controls) showed reduced activation in middle frontal gyrus and left dorsolateral prefrontal cortex, and increased activation in anterior cingulate cortex, in the LLD group compared with controls in a study examining activation during an eStroop task. This was mediated by cognitive reserve such that greater cognitive reserve correlated with greater middle frontal gyrus activation in the LLD group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations